2022
DOI: 10.3389/fpsyg.2022.892346
|View full text |Cite
|
Sign up to set email alerts
|

Uyghur–Chinese Adult Bilinguals’ Construal of Voluntary Motion Events

Abstract: The study examined the implications of Talmy motion event typology and Slobin’s thinking-for-speaking hypothesis for the context of Uyghur–Chinese early successive bilingualism. Uyghur and Chinese represent genetically distant languages (Turkic vs. Sino-Tibetan) that nonetheless share important framing properties in the motion domain, i.e., verb-framing. This study thus aimed to establish how this structural overlap would inform bilingual speakers’ construal of motion events. Additionally, it sought to offer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 71 publications
4
9
0
Order By: Relevance
“…The unique language combination enabled us to demonstrate that CLI can happen in languages that are genetically distant (Turkic vs. Sino-Tibetan) and typologically distinct (agglutinative vs. analytical), and that when there is a clear structural overlap between languages, CLI can be largely quantitative (i.e., more frequent use of a particular structure), not qualitative (i.e., use of suboptimal or target-deviant structures). A comparison with Tusun's (2019) study on Uyghur-Chinese child bilinguals' expression of CM noted an increase of this CLI from child to adult bilinguals, which we interpreted as supporting the coactivation account. However, further comparisons of our findings with those of an earlier study on Uyghur-Chinese adult bilinguals' VM expression (Tusun, 2022a) revealed that, while structural overlap is a key motivating factor for CLI, neither of the two hypotheses can comprehensively explain patterns of CLI we see across event types (CM vs. VM) and age groups in Uyghur-Chinese bilingualism.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The unique language combination enabled us to demonstrate that CLI can happen in languages that are genetically distant (Turkic vs. Sino-Tibetan) and typologically distinct (agglutinative vs. analytical), and that when there is a clear structural overlap between languages, CLI can be largely quantitative (i.e., more frequent use of a particular structure), not qualitative (i.e., use of suboptimal or target-deviant structures). A comparison with Tusun's (2019) study on Uyghur-Chinese child bilinguals' expression of CM noted an increase of this CLI from child to adult bilinguals, which we interpreted as supporting the coactivation account. However, further comparisons of our findings with those of an earlier study on Uyghur-Chinese adult bilinguals' VM expression (Tusun, 2022a) revealed that, while structural overlap is a key motivating factor for CLI, neither of the two hypotheses can comprehensively explain patterns of CLI we see across event types (CM vs. VM) and age groups in Uyghur-Chinese bilingualism.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, we mentioned that this study hopes to offer more general remarks on the nature of CLI by comparing its findings with those of an earlier study (Tusun, 2022a) where the same adult bilinguals followed the same experimental procedure as this study but verbalized a set of VM events. Specifically, Tusun found that the bilinguals followed the monolingual Chinese pattern of predominantly using the equipollently-framed strategy, and thus showed no CLI.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations